An Integrated Dual Antenna for Multi-Band Satellite Communication Applications - Chitambara Rao, Karedla; Nataraj, Dasari; Chakradhar, K. S.; Ujwala, G. Vinutna; Sudhir, B.; Lakshmunaidu, M.; Dadi, Harihara Santosh (Engineering, Technology & Applied Science Research, 2025)
Satellite communication applications for a variety of platforms are expanding quickly as the current technology and the demand for multi-band antennas are driving up. Multi-band antennas are likely to be required for the majority of communication systems including commercial, amateur, and military ones. For military communications, various antennas are employed on a mast to cover different bands, particularly the multifunction mast-mounted antennas that are based on submarines. However, there will be limited space on the mast in case different antennas are used for different frequencies, a limitation which will restrict the ability of the submarine-based multifunction mast-mounted antenna to cover the different bands. Thus, instead of employing different antennas for different bands, a multi-band antenna can be used to compensate for the space limitation. Modern submarines should also be able to communicate with satellites. Designing an antenna for satellite communication is difficult because successful operation necessitates specific characteristics, such as low axial ratio, low Voltage Standing Wave Ratio (VSWR), high gain, high band width, and high 3 dB beam width. This work proposes an inventive design approach for an integrated dual antenna on a single ground for two bands, the L-Band and S-Band. The latter cover the five satellite communication applications, including sending (2500-2520 MHz) and receiving (2670-2690 MHz) bands of S-Band satellite communication, the Global Positioning System (GPS)-1575.42 MHz, the Global Navigational Satellite System (GNSS)-1610 MHz, and the Indian Regional Navigational Satellite System (IRNSS)-1176.5 MHz. To examine important characteristics, including VSWR, gain, axial ratio, and 3 dB beam width, a simulation of an integrated dual antenna is constructed. The parameters are examined after the simulation in order to assess the proposed antenna’s performance. The analysis results indicate that the proposed antenna is suitable for a variety of satellite communication applications, and highly suitable for both the L-Band and S-Band.